STATUS PEMANFAATAN PERIKANAN KEPITING MERAH (Scylla olivacea) DI PERAIRAN MIMIKA DAN SEKITARNYA, PAPUA - Andina Ramadhani Putri Pane; Reza Alnanda; Ali Suman (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
Red mud crab (Scylla olivacea) is an economic commodity that is traded into foreign countries such as China, Malaysia, and Singapore so that fishing activities are carried out intensively. Therefore, we need scientific information about the status of red mud crab fishery stock. Information about the natural mortality, fishing mortality, and the exploitation level of crabs can be used as the basis for crab fisheries management. The study was conducted for 2 (two) years, February to October 2017, and March to December 2018 using the survey method. The results showed that 36% of the crabs were caught below the 120 mm size as regulated in Regulation of the Minister of Marine Affairs and Fisheries No. 12 Year 2020. The carapace width of the first capture (CWc) is smaller than the size of the carapace width of the first gonad maturity (CWm). This shows that the crab has been captured before the first gonad maturity (CWc < CWm). The growth rate (K) is 0.65 per year with fishing mortality (F) higher than natural mortality (M). Exploitation level (E) 0.70 which indicates that the status fisheries of red mud crab in Mimika have been overexploited. Efforts need to be done by the Regional Government in collaboration with local community leaders in providing counseling and information about the size of red mud crabs that can be caught and reduce efforts to use crabs by as much as 40% of what is currently done. Keywords: status explotation, red mud crabs, Mimika, FMA 718